Floristic Composition and Diversity of Agroforestry Based Agarwood (Gyrinops versteegii) in Bantul, Yogyakarta - Rawana; Agus Prijono; Setiaji Heri Saputra; Siti Maimunah; Nanda Satya Nugraha; Hastanto (Journal of Sylva Indonesiana, 2026)
Gyrinops versteegii is one of the agarwood-producing trees with high economic value, however including CITES appendix II, quotas limit trade. This research aims to determine the composition and diversity of the species that make up agarwood-based home garden agroforestry practices and to determine the similarity of communities in two sites, namely in Parangtritis village and Sawo hamlet, Bantul district, Yogyakarta. The research was conducted in Parangtritis village, Kretek District and Sawo hamlet, Banguntapan District, Bantul Regency, Yogyakarta. Sampling was used using the plot method with a plot measuring 20 x 20 m2, which was placed purposely. The species diversity index uses Shannon’s index formula, while the evenness index uses the Alatalo index. The species of richness index used is Margalef’s index. Meanwhile, community similarity is used by Sorensen’s index and Jaccard’s index. This research found that the number of species that make up gaharu-based home garden agroforestry practices is 24 tree species, with 296 individuals belonging to 22 genera and 18 families. The diversity index of home garden species in Parangtritis and Sawo is categorized as medium with an H" value of 1.46 and 1.87, respectively. Likewise, the index values for the evenness of home garden species in Parangtritis and Sawo are 0.59 and 0.65, respectively, categorized as moderate. The species richness index in Parangtritis (2.015) is lower than in Sawo (4.119). The Sorensen similarity index value of 0.4 is categorized as medium, while according to the Jaccard index of 0.25, it is categorized as low. These findings suggest the need for improved species selection and management practices to enhance agroforestry sustainability and biodiversity conservation